Community and Social Context: An Important Social Determinant of Cardiovascular Disease - *Rahul Singh; *Zulqarnain Javed; Tamer Yahya; Javier Valero-Elizondo; Isaac Acquah; Adnan A. Hyder; Muhammad Haisum Maqsood; Zahir Amin; Sadeer Al-Kindi; Miguel Cainzos-Achirica; Khurram Nasir (Methodist DeBakey Cardiovascular Journal)
Disease prevention frameworks and clinical practice guidelines in the United States (US) have traditionally ignored upstream social determinants of health (SDOH), which are critical for reducing disparities in cardiovascular disease (CVD)—the leading cause of death in the US. Existing evidence demonstrates a protective effect of social support, social cohesion, and community engagement on overall health and wellbeing. Increasing community and social support is a major objective of the Healthy People 2030 initiative, with special provisions for vulnerable populations. However, to date, existing evidence of the association between community and social context (CSC)—an integral SDOH domain—and CVD has not been reviewed extensively. In particular, the individual and cumulative impact of CSC on CVD risk and the pathways linking CSC to cardiovascular outcomes are not well understood. In this review, we critically appraise current knowledge of the association between CSC and CVD, describe potential pathways linking CSC to CVD, and identify opportunities for evidence-based policy and practice interventions to improve CVD outcomes.